Inventory up-keeping with AR interface - Ng, Zheng (2024)
Internet of Things (IoT) devices are being rapidly adopted in homes to provide automation, security, energy savings and convenience. However, the proliferation of heterogeneous devices and platforms poses challenges for effective monitoring and control. Traditional 2D dashboards on desktops/mobiles have limitations in visualizing complex IoT networks and data. This paper proposes an AR-based solution using the Oculus Quest and Home Assistant platform to enhance the management experience. The goal is to develop an intuitive AR interface that overlays 3D visualizations directly onto physical environments for improved visibility. Real-time sensor data will be aggregated from various IoT systems into the Home Assistant and streamed into the AR environment via API integration. The AR dashboard will provide at-a-glance monitoring and controls tailored to IoT tasks. A user-centered iterative design process will be followed incorporating performance benchmarking, usability metrics, and user experience feedback. The Unity game engine will be utilized to render an immersive 3D user interface registered to real-world coordinates. Consolidating insights into a unified AR dashboard aims to simplify smart home management. The project will showcase techniques like natural interactions applied in a practical IoT context, guiding future AR interface and visualization design. Findings will reveal AR's advantages over traditional methods for visualizing complex systems and data, monitoring situational awareness, and enabling intuitive control. This approach of combining AR and IoT provides a model for developing next-generation interfaces to optimize IoT management. Insights gained can inform solutions for managing growing consumer IoT ecosystems spanning diverse devices, standards, and vendors.